Variation of small erect-fruited chili in Thailand - Milerue, Nongluck; Chunwongse, Julapark; Struss, Darush; Wasee, Sirikul (Agriculture and Natural Resources, 2016)
Single cross varieties of small, erect-fruited chili (Prik-khee-noo in Thai) are required because of their high yield and high quality. Production of a single cross needs superior parental lines. This study was conducted to screen for parental lines which could be used for the production of superior single cross. To develop new varieties, high variation of the parental lines is required. Twenty-eight chili accessions (Capsicum annuum L.) cultivated in Thailand were collected and evaluated for variation with 343 single nucleotide polymorphic (SNP) markers at the Molecular Marker Laboratory at Hortigenetic Research (S.E. Asia) Ltd., Chiang Mai, Thailand. The results showed low variation among the 28 chili accessions with the polymorphism information content varying from 0.45 to 0.49 with an average of 0.46. The average genetic distance estimated from the SNP markers based on Jaccard's coefficient was 0.29 (ranging from 0.03 to 0.55). However, based on SNP analysis, the unweighted pair-group method with arithmetic averages divided the 28 chili accessions into two main groups and four subgroups. The first group consisted of 23 accessions mostly collected from varieties cultivated in Northeastern Thailand. The second group contained five accessions collected from different locations in other regions of Thailand.